Integration of Rule Based and Sensor Based Control for a Six-Legged Insect-Like Robot - Pitikhate Sooraksa; Kangwan Saensawasd; Sorapon Bunjongsena Na Ayuttaya (My University, 2000)
Integration of Rule Based and Sensor Based Control for a Six-Legged Insect-Like Robot Pitikhate Sooraksa, Kangwan Saensawasd, Sorapon Bunjongsena Na Ayuttaya Pages 1-4 (2000 Proceedings of the 17th ISARC, Taipei, Taiwan, ISBN 9789570266986, ISSN 2413-5844) Abstract: This paper proposes the rule based and sensor based control strategies for a six-legged insect-like robot. This control scheme emulates the well-known insect behavior called ?the reflex action.? Three types of sensors are embedded in the body of the robot, which are infrared sensors, ultrasonic sensors and limit switches for tracking performance, collision avoidance, and touching perception, respectively. The walking and acting features are driven by servomotors using sets of common-sense instructions or rules. The results show that the satisfactory performance is achieved with this control approach. This implies that the designed robotic system can be used to perform inspection, maintenance or repair in construction tasks. Keywords: insect-like robot, reflex control, walking robot, rule based control, sensor based control DOI: https://doi.org/10.22260/ISARC2000/0058 Download fulltext Download BibTex Download Endnote (RIS) TeX Import to Mendeley
Keywords: Robot Manipulation and Learning